2021
DOI: 10.1186/s13223-021-00584-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of ileal mucosa in asthma reveals upregulation of innate immunity and genes characteristic of Paneth and goblet cells

Abstract: Background The expression profiles of the intestinal mucosa have not been comprehensively investigated in asthma. We aimed to explore this in the Correlated Expression and Disease Association Research (CEDAR) patient cohort. Methods Differential expression analysis of ileal, transverse colon, and rectal biopsies were supplemented by a comparison of transcriptomes from platelets and leukocytes subsets, including CD4+, CD8+, CD14+, CD15+, and CD19+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Previous studies have found that tetrahydrocurcumin (THC) treatment reduced the relative abundance of the pro-inflammatory bacterium Intestinimonas in the gut of OVA-induced mice, thereby reducing Th2-mediated inflammation [39]. In previous studies on the expression profiles of intestinal mucosa in asthma, the authors found only overexpressions of innate immune genes in the ileum in the differential expression of ileum, transverse colon, and rectum biopsies [40]. The stability of the gut microbiota contributes to the intestinal mucosal barrier and nutrient uptake function, thereby maintaining immune balance [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that tetrahydrocurcumin (THC) treatment reduced the relative abundance of the pro-inflammatory bacterium Intestinimonas in the gut of OVA-induced mice, thereby reducing Th2-mediated inflammation [39]. In previous studies on the expression profiles of intestinal mucosa in asthma, the authors found only overexpressions of innate immune genes in the ileum in the differential expression of ileum, transverse colon, and rectum biopsies [40]. The stability of the gut microbiota contributes to the intestinal mucosal barrier and nutrient uptake function, thereby maintaining immune balance [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find significant results for KDM4C and MYL7. ATF3 [111,112], BCL6 [113,114], EGR1 [115,116], ELF3 [117], EP300 [118,119], FOXA1 [93], FOXA2 [94,95], FOXA3 [94,120], HDAC2 [121,122], IRF2 [123], JUND [124,125], KAT8 [126,127], NFIL3 [103,104], NFYC [128], PRDM1 [129,130], RAD21 [131,132], RARA [105], RXRA [100,101], RXRB [133], SMAD4 [106], SP1 [134], THRB [135,136], YY1 [137,138] a The CADD PHRED score 10 means risk of top rank 10%, 20 means risk of top rank 1%; b the DANN score ranges from 0 to 1, where 1 represents the highest possibility for pathogenicity; c asthma-related transcription factor that controls the rate of transcription of genetic information from DNA to messenger RNA by binding to a specific DNA sequence; d scores range from 1 to 7, with lower values indicating that the variant is more likely to be located in the functional region.…”
Section: Functional Annotationmentioning
confidence: 99%